Distribution, assembly, and interactions of soil microorganisms in the bright coniferous forest area of China's cold temperate zone - Rao, Gu; Yan, Shu-Zhen; Song, Wen-Long; Lin, Di; Chen, Ya-Jing; Chen, Shuang-Lin (The Science of the total environment, 2023)
The bright coniferous forest area in the cold temperate zone of China is a terrestrial ecosystem primarily dominated by low mountain Larix gmelinii trees. Limited information is available regarding the assembly mechanisms and interactions of microbial communities in the soil in this region. This study employed high-throughput techniques to obtain DNA from myxomycetes, bacteria, and fungi in the soil, evaluated their diversity in conjunction with environmental factors, associated them with the assembly process, and explored the potential interaction relationships between these microorganisms. The findings of our study showed that environmental factors had a more significant influence on the α and β diversity of bacteria compared to myxomycetes and fungi. Microbial communities were influenced by environmental selection and geographical diffusion, although environmental selection appeared to have a more significant impact than geographical diffusion. Our study suggested that different microorganisms exhibited unique evolutionary patterns and may have different assembly modes within phylogenetic groups. Myxomycetes and fungi exhibited a similar assembly process that was mainly influenced by stochastic dispersal limitation and drift. In contrast, bacteria's assembly process was primarily influenced by stochastic drift and deterministic homogeneous selection. The community of myxomycetes and fungi is greatly influenced by spatial distribution and random events, while bacteria have a relatively stable population composition in specific regions and may also be subject to environmental constraints. Finally, this study revealed that Humicolopsis cephalosporioides, a fungus that exclusively resided in cold environments, may play a critical role as a keystone species in maintaining molecular ecological networks and was considered a core member of the microbiome. [Display omitted] •Environmental selection had a greater impact on the microbial community than geographical diffusion.•Myxomycetes, fungi, and bacteria exhibited distinct assembly processes.•Myxomycetes and fungi were primarily influenced by spatial distribution and random events.•Bacteria had stable composition in specific regions, possibly due to environmental constraints.•Humicolopsis cephalosporioides may have essential ecological functions and values.